2022
DOI: 10.3389/fmicb.2022.822254
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Two New Acyl-CoA:Diacylglycerol Acyltransferase 2-Like Acyl-CoA:Sterol Acyltransferases Enhanced Squalene Accumulation in Aurantiochytrium limacinum

Abstract: Thraustochytrids are heterotrophic marine eukaryotes known to accumulate large amounts of triacylglycerols, and they also synthesize terpenoids like carotenoids and squalene, which all have an increasing market demand. However, a more extensive knowledge of the lipid metabolism is needed to develop thraustochytrids for profitable biomanufacturing. In this study, two putative type-2 Acyl-CoA:diacylglycerol acyltransferases (DGAT2) genes of Aurantiochytrium sp. T66, T66ASATa, and T66ASATb, and their homologs in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 47 publications
(69 reference statements)
1
8
0
Order By: Relevance
“…SD116 and T66ASATb from Aurantiochytrium sp. T66 with protein identities of 68.4% and 77.6%, respectively. Further investigations are needed to determine whether ScDGAT2–1 has more functions.…”
Section: Resultsmentioning
confidence: 99%
“…SD116 and T66ASATb from Aurantiochytrium sp. T66 with protein identities of 68.4% and 77.6%, respectively. Further investigations are needed to determine whether ScDGAT2–1 has more functions.…”
Section: Resultsmentioning
confidence: 99%
“…Rau et al reported that dysfunction of AlASATb, which was found as a DGAT2 homolog, significantly reduced the intracellular SE level in A. limacinum SR21 and suggested that AlASATb was an acyl-CoA:sterol- O -acyltransferase (ASAT) ( 27 ). To further understand the functions of DGAT2 homologs, the C-terminal FLAG-tagged dgat2c and dgat2d were expressed in S. cerevisiae , and their expressions were examined by Western blotting using an anti-FLAG-tag antibody.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that the control of this pathway in thraustochytrids (SR21) differs from that in other species. These results suggest a more complex relationship between the squalene and carotenoid biosynthetic pathways than merely competition for the same precursors [47].…”
Section: Limitations Of Genetic Modification In Thraustochytrids For ...mentioning
confidence: 90%
“…The flavoprotein squalene epoxidase catalyzes the first oxygenation reaction and rate-limiting step in this pathway. Downregulation or knockout of the genes responsible for the conversion of squalene to sterols and further to steryl esters has been shown to change the overall titer of squalene in yeast and the thraustochytrid Aurantiochytrium limacinum SR21 [47,48]. Steryl esters are synthesized by acyl-CoA:sterol acyltransferase (ASAT) through acylation of the hydroxyl group at the C3-position of sterols [48].…”
Section: Downregulation Of Squalene Epoxidasementioning
confidence: 99%
See 1 more Smart Citation